THE FORMS OF CLASSROOM INTERACTION FOUND IN ENGLISH CLASSROOM AT SMA NEGERI IN BENGKULU (A Comparative Study between Favorite and Un-Favorite Schools in Bengkulu) - Pistarman Pistarman (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
The problems of this research are: how is the interaction done by the teacher and students inEnglish classroom in SMA Negeri in Bengkulu?and what are the differences (if any) of theinteraction process found in favorite SMA an un-favorite SMA in Bengkulu? the purpose of thisresearch is: to describe the interaction between teacher and students and to describes thedifferences between the interaction. The forms of classroom interaction were taken fromMalcolm, 1997 and Roestiyah, 1994. They accepting feeling, complement and encouragement,accepting or uses ideas of students, asking the studentsabout the procedure or content of study,lecturing, giving direction to the students, criticizing or justifying authority, students response,students initiative, answering question, silence and confusion, one way interaction, multi wayinteraction.The design of this research was descriptive method; descriptive method is a survey orobservation that describes the situation as being observed. The population of this research isEnglish teachers and the second year students of senior high school in favorite and in unfavoriteschools. They are SMAN 2 Bengkulu, with 190 students in 8 classes and SMAN 6Bengkulu, with 150 students in 6 classes. The sample of this research is used randomlysampling, from SMAN 2 Bengkulu is an English teacher and 42 students and from SMAN 6Bengkulu is an English teacher and 44 students.The result of this study shown that, the forms of interaction that dominant used by the teacherand students interaction in the classroom at SMAN 2 Bengkulu and SMAN 6 Bengkulu. Thoseare teacher asking question 64 times (19,16%) and 33 times (15,94%) the teacher ask tostudents about procedure and content of study. Students answer question 57 times (17,06%)and 27 times (13,04%), two way interaction 55 times (16,47%) and 29 times (14,01%), howeverthere is form of interaction that dominant used in SMAN 6 Bengkulu but it is not dominant usedin SMAN 2 Bengkulu. It is lecturing 18 times (8,69%) the significant differences between SMAN2 and SMAN 6 Bengkulu interaction, can see from the result in frequency, at SMAN 2 Bengkuluhigher than SMAN 6 Bengkulu, it is caused at SMAN 6 Bengkulu students and teacherinteraction done slowly or teaching and learning process done slowly. Sometimes the teacherand students discuss about something that is not relationship with material being taught.